2022
DOI: 10.1007/s12325-022-02364-2
|View full text |Cite
|
Sign up to set email alerts
|

Burden of Fatigue Among Patients with Ulcerative Colitis and Crohn’s Disease: Results from a Global Survey of Patients and Gastroenterologists

Abstract: Introduction To assess the prevalence of fatigue and its association with disease activity and patient-reported outcomes among patients with ulcerative colitis (UC) or Crohn’s disease (CD). Methods Data from a cross-sectional survey conducted with gastroenterologists and their consulting adult patients with UC or CD were analyzed. Data were collected via gastroenterologist-completed patient record forms and patient-self completion forms. Patient demographics, clinical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…For correlation between simple clinical colitis activity, fatigue severity and quality of life on post program, the present study clarified that there was a significant positive correlation between simple clinical colitis activity and fatigue severity among the study group. This result was in accordance with Regueiro et al, (2023) who found that there was a significant positive relationship between clinical disease activity and fatigue. A higher percentage of patients with UC and fatigue had moderate/severe clinical disease activity.…”
Section: Outcomes During Remission Phasesupporting
confidence: 92%
“…For correlation between simple clinical colitis activity, fatigue severity and quality of life on post program, the present study clarified that there was a significant positive correlation between simple clinical colitis activity and fatigue severity among the study group. This result was in accordance with Regueiro et al, (2023) who found that there was a significant positive relationship between clinical disease activity and fatigue. A higher percentage of patients with UC and fatigue had moderate/severe clinical disease activity.…”
Section: Outcomes During Remission Phasesupporting
confidence: 92%
“…Fatigue is a prominent feature of autoimmune diseases and is a large area of focus in rheumatoid arthritis (RA) and ulcerative colitis (UC) research [1, 2]. There is an extensive body of previously published work exploring neuroimaging in these chronic inflammatory diseases looking to identify surrogate biomarkers of disease linked to fatigue [3].…”
Section: Introductionmentioning
confidence: 99%
“…Ulcerative colitis (UC), also known as chronic non-specific UC, is an unexplained rectal and colitis lesion, which has been classified as one of the modern refractory diseases by the world Health Organization (WHO) and seriously affects the normal life of patients (Regueiro et al, 2023). Clinically, it is mainly characterized by recurrent abdominal pain, diarrhea, mucopurulent bloody stools, tenesmus and so on.…”
Section: Introductionmentioning
confidence: 99%